Squared Weyl and Dirac fields with the Sommers-Sen connection associated with V³₄ distributions - Pelykh, V. (Condensed Matter Physics, 1998)
Generalization of the Sommers–Sen spinor connection for spinor fields,
associated with the distribution V³₄ is made and on its basis the equations for Weyl and Dirac null vector fields on complexificated V³₄ are obtained. We interpret the obtained results by examining the interaction of spinor fields with inertial forces. На основі узагальнення спінорної зв’язності Соммерса-Сена для полів, асоційованих із розподілом V³₄ , отримано рівняння для нульових полів Вейля і Дірака у комплексифікованому розподілі V³₄ . Отримані рівняння дозволяють описати взаємодію нульових полів із полями інерції.